Content Aspects of the Alternative Concept of Tax Regulation: Neo-Industrial Growth and Primary Implements for Fulfillment - E. Yu. Sidorova (Учёт. Анализ. Аудит, 2023)
The changes have being taken place in the social and economic life of the world community and the transition to a neo-industrial type of growth, as well as the need to localize the consequences of COVID-19 require the tax regulation system transformation together with the formation of new tools that meet modern realities. The objectives of the study are to consider the substantive aspects of the alternative concept of tax regulation of neo-industrial development and to determine the fundamental mechanisms for its implementation. The author analyzed the features of the latter, identified the possibilities of the apply to reach the goal and proposed measures to adapt them to new conditions. The paper presents the basic elements of an alternative concept of tax regulation, which includes three components: man — production — society, as well as goals: resource saving, recycling, labor-saving motivation, energy efficiency of the economy, circular economy, and taxes: para-fiscal economy (recycling fee, ecological tax), system of resource taxes (carbon tax, payment for negative environmental impact), excise tax on fuels and lubricants, tax on natural resources. The author highlighted that neo-industrial development is largely facilitated by the transition from the supportive taxation regime to the stimulating one. The work used methods of analysis (including comparative) and analogy. The practical significance of the work lies in the development of a general characteristic of the tax regulation concept.